The Mining Concession and the Right of Exploitation Seeking a Balance between the Public and the Private - Salazar Niño, Elvis (2014)
The author introduces the regulatory and political landscape of the mining concession and the institutional decay it has suffered. He also shows the systems of acreage and the system which our country has received it well: the System of Public Domain. Finally, the author analyzes the mining concession and harvesting rights, raised according to the Constitution and the General Mining Law, explaining the policy changes needed to strengthen it as a fundamental qualifying title for the development of mining activities in the country.